Extended Curriculum Evolution: A Road Map to Academic Success? - Slabbert, Roan; Friedrich-Nel, Hesta (South African Journal of Higher Education, 2016)
The extended curriculum programme (ECP) in the faculty of Health Sciences at the Central University of Technology (CUT), Bloemfontein, consists of six (6) different instructional programmes. These programmes have been developed for Biomedical Technology, Clinical Technology, Emergency Medical Care, Environmental Health, Radiography and Somatology. This article provides an overview of the progress and development of the ECP in the Health Sciences at CUT as a proposed road map to academic success for a specific group of students. To obtain an objective picture of students’ success in the ECP in the Health Sciences, the assessment results of all the students registered between 2007 and 2012 were retrieved and analysed retrospectively. An increase in articulation was noted from 2010 to 2012 (i.e., from 70% to 84.4%) and an average articulation percentage of 80% was achieved from 2007 to 2012. These figures indicate a successful transition from ECP to the mainstream programmes. Moreover, 58% of ECP students who registered in 2007 successfully completed their national diplomas in the extended timeframe. This group also delivered three B-Tech candidates and one student registered for a Master’s Degree. The emotional growth and personal development of students were also prominent, as observed by mainstream lecturers. The support offered to students in the current ECP model includes a mentorship programme with a qualified psychologist, supplemental instruction (SI) and the sponsorship of all textbooks and registration fees for the Health Professions Council of South Africa (HPCSA) and first aid training.